Psychological Well-Being pada Siswa Broken Home - Yuanita Armasari Muslih; Heri Saptadi Ismanto; Lyanna Oktavia T (Universitas PGRI Palembang, 2024)
Families that are not intact either diminish or increase and are unable to perform their roles optimally to meet their needs related to affection, emotional, and financial can have an impact and affect the psychological well-being of individuals. Psychological well-being can be interpreted as a condition in which a person feels comfortable with attitudes such as accepting oneself, purposeful, establishing positive relationships, independent, and developing This study aims to determine and describe the psychological well-being of students who experience broken homes. This research uses qualitative methods with a fenomenology study design. Participants were selected using purposive sampling techniques with characteristics of adolescence, the same grade level and coming from broken home. Participants amounted to three people, namely in the age range of 16 to 18 years. Collection of research data by means of in-depth interviews and participant observation. The results showed that the three participants had different aspects of psychological well-being. NSF's psychological well-being is positive, RTK is more positive while ZPD is less positive.